The Effect of Using PVAc (Polyvinyl Acetate) & Epoxy Resin Adhesives on the Shear Strength of Laminated Bamboo - Darwis, Zulmahdi; Soelarso, Soelarso; Riyadi, Andry Afrizal (JURUSAN TEKNIK SIPIL, 2024)
The use of wood as a construction material is common throughout Indonesia. Based on this, wood material is easy to obtain and wood material itself can make buildings look more attractive. Wood as a source of materials for both construction and non-construction makes the price of wood increase and makes rainforests that function to protect the environment threatened with loss as well as the ecosystem in it. One material that is suitable for replacing wood is bamboo. Bamboo is easy to plant, breed, fast in growth, and of course the price is relatively cheap. The hollow or empty interior of bamboo often makes it difficult for users to utilise bamboo, therefore bamboo lamination technology is applied to facilitate the manufacture of building construction components. The purpose of this study is to determine the shear strength value of bamboo laminates using PVAc adhesive and epoxy resin adhesive and to determine the damage pattern on bamboo laminated beams after shear strength testing when using PVAc adhesive and Epoxy Resin adhesive. The tests carried out refer to SNI 03-3400-1994 using test specimens in the form of laminated bamboo beams with 2 variations of lamination, namely with PVAc and epoxy resin adhesives. Based on the tests carried out, the shear strength of laminated bamboo beams using epoxy resin adhesive is stronger with an average value of 6.7206 MPa compared to laminated bamboo beams using PVAc adhesive with an average value of 2.7949 MPa. The damage pattern that occurs in the adhesive part is damaged during maximum load with the bamboo slats detaching from the adhesive in the epoxy resin adhesive and in the PVAc adhesive the glue part is lifted.